Geographical Accessibility of Pediatric Inpatient, Nephrology, and Urology Services in Europe - Terliesner, Nicolas; Lesniowski, Dariusz; Krasnikova, Alexandra; Korte, Martin; Terliesner, Mirjam; Mall, Marcus A.; Dittrich, Katalin (Frontiers in Pediatrics, 2020)
Background: Although many children with diseases of the kidneys and the urinary tract may not tolerate long journeys, the number of facilities that provide specialized care for these patients is limited. Therefore, the geographical accessibility of the required health services is critical especially in this patient group. We have analyzed the geographical accessibility of pediatric inpatient and nephro-urology services in Germany, Ireland, and the United Kingdom (UK). Methods: This study introduces a model to compare countries or regions regarding the geographical accessibility of their health services. We calculated the geodesic distances, travel distances, and travel time by car from evenly distributed random points to the nearest facilities that provide pediatric inpatient or nephro-urology outpatient services (pediatric inpatient ward, urology clinic, nephrology clinic, hemodialysis unit). The results were weighted by population density. We compared the three countries with regard to the accessibility of the named services. Results: Weighted median travel times from the random points to the nearest pediatric inpatient ward are less than 30min in all countries. Weighted travel times to the nearest point of pediatric service are shortest in the UK (median <50min) and longest in Ireland (median <90min), regardless of the type of service (p <0.0001). Non-weighted travel times to the nearest pediatric inpatient ward and hemodialysis unit, however, are shorter in Germany than in the UK (p <0.0001). Conclusions: There is a surprising disparity between the travel times to the nearest facility with pediatric nephro-urology service in these three industrialized European countries. Reasons may be differences in the geographical distribution of the population, the focus of the health care system, and a different degree of clinical networking.